Characterization and Expression of Genes Involved in the Ethylene Biosynthesis and Signal Transduction during Ripening of Mulberry Fruit - Liu, Changying; Zhao, Aichun; Zhu, Panpan; Li, Jun; Han, Leng; Wang, Xiling; Fan, Wei; Lü, Ruihua; Wang, Chuanhong; Li, Zhengang; Lu, Cheng; Yu, Maode (PLOS ONE, 2015)
Although ethylene is well known as an essential regulator of fruit development, little work has examined the role ethylene plays in the development and maturation of mulberry (Morus L.) fruit. To study the mechanism of ethylene action during fruit development in this species, we measured the ethylene production, fruit firmness, and soluble solids content (SSC) during fruit development and harvest. By comparing the results with those from other climacteric fruit, we concluded that Morus fruit are probably climacteric. Genes associated with the ethylene signal transduction pathway of Morus were characterized from M. notabilis Genome Database, including four ethylene receptor genes, a EIN2-like gene, a CTR1-like gene, four EIN3-like genes, and a RTE1-like gene. The expression patterns of these genes were analyzed in the fruit of M. atropurpurea cv. Jialing No.40. During fruit development, transcript levels of MaETR2, MaERS, MaEIN4, MaRTE, and MaCTR1 were lower at the early stages and higher after 26 days after full bloom (DAF), while MaETR1, MaEIL1, MaEIL2, and MaEIL3 remained constant. In ripening fruit, the transcripts of MaACO1 and MaACS3 increased, while MaACS1 and MaACO2 decreased after harvest. The transcripts of MaACO1, MaACO2, and MaACS3 were inhibited by ethylene, and 1-MCP (1–methylcyclopropene) upregulated MaACS3. The transcripts of the MaETR-like genes, MaRTE, and MaCTR1 were inhibited by ethylene and 1-MCP, suggesting that ethylene may accelerate the decline of MaETRs transcripts. No significant changes in the expression of MaEIN2, MaEIL1, and MaEIL3 were observed during ripening or in response to ethylene, while the expressions of MaEIL2 and MaEIL4 increased rapidly after 24 h after harvest (HAH) and were upregulated by ethylene. The present study provides insights into ethylene biosynthesis and signal transduction in Morus plants and lays a foundation for the further understanding of the mechanisms underlying Morus fruit development and ripening.